2021
DOI: 10.3390/v13122520
|View full text |Cite
|
Sign up to set email alerts
|

Natural Coinfection between Novel Species of Baculoviruses in Spodoptera ornithogalli Larvae

Abstract: Spodoptera ornithogalli (Guenée) (Lepidoptera: Noctuidae) is an important pest in different crops of economic relevance in America. For its control, strategies that include chemicals are usually used; so, the description of entomopathogens would be very useful for the formulation of biopesticides. In this regard, two different baculoviruses affecting S. ornithogalli were isolated in Colombia, with one of them being an NPV and the other a GV. Ultrastructural, molecular, and biological characterization showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…The first recorded case of co-infection of a lepidopteran larva with polyhedrosis and granulosis viruses was in the cutworm Euxoa segetum in 1936 [ 19 ]. Similar findings were reported in Pieris rapae , Pseudaletia unipuncta , Nephelodes emmedonia , Mythimna unipuncta , Choristoneura fumiferana , Spodoptera frugiperda, and Spodoptera Ornithogalli [ 20 , 21 , 22 , 23 , 24 , 25 ]. On the other hand, the experimental co-infection with two baculoviruses isolated from the same host started with the work of Tanada [ 22 , 23 ].…”
Section: Baculovirus Interactions In Vivosupporting
confidence: 86%
See 2 more Smart Citations
“…The first recorded case of co-infection of a lepidopteran larva with polyhedrosis and granulosis viruses was in the cutworm Euxoa segetum in 1936 [ 19 ]. Similar findings were reported in Pieris rapae , Pseudaletia unipuncta , Nephelodes emmedonia , Mythimna unipuncta , Choristoneura fumiferana , Spodoptera frugiperda, and Spodoptera Ornithogalli [ 20 , 21 , 22 , 23 , 24 , 25 ]. On the other hand, the experimental co-infection with two baculoviruses isolated from the same host started with the work of Tanada [ 22 , 23 ].…”
Section: Baculovirus Interactions In Vivosupporting
confidence: 86%
“…However, this synergy was observed only when the proportion of SpfrGV in the mixture did not exceed 2.5% [ 24 ]. Similar results were obtained through bioassays using SporNPV and SporGV on neonate larvae of Spodoptera ornithogalli [ 25 ].…”
Section: Baculovirus Interactions In Vivosupporting
confidence: 82%
See 1 more Smart Citation
“…Several studies (e.g., Hodgson, et al, 2004;Simon, et al, 2005 ) have shown that combination of wild type viruses has always more pathogenic than any of the individual one, suggesting a positive interaction between them. Barrera, et al (2021), mentioned that, the both viruses NPV and GV are individually infective to Spodoptera ornithogalli (Guenée) larvae but coexist in nature, producing mixed infections with a synergistic effect that improves the performance of the NPV and enables the transmission of the GV, which presents a slowly killing phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 297 genomes thus selected, 1 sequence (Lymantria dispar multiple nucleopolyhedrovirus isolate T3; accession number MF311096.1) was discarded because, according to the database file, it did not encode LEF-5 (core gene) due to mutations (“nonfunctional lef-5 due to mutation”), without an associated scientific publication endorsing this particularity. In addition, a novel sequence (SporGV) [ 23 ], obtained by our working group and not yet submitted to GenBank, was included. Therefore, a database (hereafter identified by the acronym BPDB for Baculovirus Proteome DataBase ) containing 297 complete baculoviral genomes and proteomes was generated as an input to determine homologous gene groups and phylogenetic inferences ( Table S1 ).…”
Section: Methodsmentioning
confidence: 99%